2006
DOI: 10.1002/ab.20138
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and social status: the moderating roles of sex and peer‐valued characteristics

Abstract: Research on peer rejection has long emphasized links between aggressive behavior and peer liking, with aggressive children and adolescents being more rejected by peers. However, recent research shows that at least some aggressive students enjoy considerable power and influence and are perceived as ''popular'' within the peer group. To understand the processes underlying links between aggression and social status, the present research considered three distinct indices of social status (social preference, percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
294
2
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(325 citation statements)
references
References 36 publications
(66 reference statements)
22
294
2
7
Order By: Relevance
“…This also suggests that copying the bullying behavior of popular children does not have a strong salutary effect on unpopular children. Previous research has also shown that popularity among peers is rooted in the combination of antisocial behavior with positive features (Dijkstra et al 2008;Vaillancourt and Hymel 2006). Therefore, imitation of negative behavior of popular adolescents without having positive features that reduce the negative effects of these behaviors on peer relations is likely to be a counterproductive strategy for adolescents to increase their status among peers.…”
Section: Discussionmentioning
confidence: 99%
“…This also suggests that copying the bullying behavior of popular children does not have a strong salutary effect on unpopular children. Previous research has also shown that popularity among peers is rooted in the combination of antisocial behavior with positive features (Dijkstra et al 2008;Vaillancourt and Hymel 2006). Therefore, imitation of negative behavior of popular adolescents without having positive features that reduce the negative effects of these behaviors on peer relations is likely to be a counterproductive strategy for adolescents to increase their status among peers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that popularity is related to physical and relational aggression both for genders (LaFontana & Cillessen, 2002;Rose et al, 2004;Vaillancourt & Hymel, 2006). It has been argued that aggression serves to establish dominance in the peer group (Card, Stucky, Sawalani, & Little, 2008;Hawley, 1999).…”
Section: Hypothesesmentioning
confidence: 99%
“…characteristics (e.g., Vaillancourt & Hymel, 2006). However, these approaches mostly used very broad dimensions -such as "class competence", which included both being smart and helping everyone (Bukowski et al, 2000) -or typically only focused on the sum score of peer-valued characteristics, such as physical attractiveness or being good at sport, which were typically also assessed using the same method as the outcomes (peer nominations).…”
mentioning
confidence: 99%